Drug resistance mechanism of kinase inhibitors in the treatment of hepatocellular carcinoma - Jiang, Lei; Li, Luan; Liu, Yongzhuang; Zhan, Meixiao; Lu, Ligong; Yuan, Shengtao; Liu, Yanyan (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) is the most common form of primary liver cancer, and it usually occurs following chronic liver disease. Although some progress has been made in the treatment of HCC, the prognosis of patients with advanced HCC is not optimistic, mainly because of the inevitable development of drug resistance. Therefore, multi-target kinase inhibitors for the treatment of HCC, such as sorafenib, lenvatinib, cabozantinib, and regorafenib, produce small clinical benefits for patients with HCC. It is necessary to study the mechanism of kinase inhibitor resistance and explore possible solutions to overcome this resistance to improve clinical benefits. In this study, we reviewed the mechanisms of resistance to multi-target kinase inhibitors in HCC and discussed strategies that can be used to improve treatment outcomes.